2015
DOI: 10.1186/s40792-015-0064-y
|View full text |Cite
|
Sign up to set email alerts
|

An incarcerated appendix and the ileocecum within a left inguinal hernia in an infant

Abstract: An 8-month-old boy with a left-sided incarcerated inguinal hernia involving the appendix, cecum, and terminal ileum was successfully managed via an inguinal approach during an emergency operation. A mobile cecum seemed to have contributed to the left-sided incarceration. Only 13 similar cases with the left-sided Amyand’s hernia have been reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…[ 2 ] “Amyand's hernia”, can appear on the left side rarely, and only 15 pediatric cases have been described in the literature. [ 3 4 ] All of the patients were males whose ages ranged from 2 to 18 months. Our patient is thus the 16 th such case and oldest patient by age among the reported cases of left “Amyand's hernia”, in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] “Amyand's hernia”, can appear on the left side rarely, and only 15 pediatric cases have been described in the literature. [ 3 4 ] All of the patients were males whose ages ranged from 2 to 18 months. Our patient is thus the 16 th such case and oldest patient by age among the reported cases of left “Amyand's hernia”, in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors also supported the presence of bilious or nonbilious vomiting and irreducible inguinal swelling in similar cases. 1 , 5 , 6 , 8 11 …”
Section: Discussionmentioning
confidence: 99%
“…17 Contrary to this, it was reported that contrast-enhanced computed tomography and a contrast enema have revealed the presence of the ileum and cecum and/or appendix within left-sided Amyand’s hernias in some adult patients. 18 – 20 Yoneyama et al, 11 on the other hand, put forward the idea that it may not be practical to perform computed tomography or a contrast enema preoperatively to rule out Amyand’s hernia in all pediatric patients with symptoms of an incarcerated hernia, and physical examination should be enough to prompt emergency operations in those patients. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations